2018
DOI: 10.1186/s12881-018-0661-2
|View full text |Cite
|
Sign up to set email alerts
|

First evidence of maternally inherited mosaicism in TGFBR1 and subtle primary myocardial changes in Loeys-Dietz syndrome: a case report

Abstract: BackgroundLoeys-Dietz syndrome (LDS) is a rare multisystemic disorder characterized by vascular and skeletal abnormalities, with considerable intra- and interfamilial variability.Case presentationWe report the case of an 8-year-old male with clinical features of two distinct genetic disorders, namely LDS, manifesting in the first months by progressive aortic root dilatation, arterial tortuosity, bifid uvula, and inguinal hernias and oculocutaneous albinism (OCA) manifesting by white hair and skin that does not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
2
5
0
Order By: Relevance
“…Regarding the occurrence of left sided heart lesions and the potential progressive aspect in our patient of aortic dilatation, these features go along with previous reports that genes which belong to TGFβ cascade are potentially prone to this subcategory of cardiac involvement (Baban et al, 2018). It might be wise to establish a specific screening program through serial electrocardiography and echocardiography detect progressive aortic dilatation or arrhythmias.…”
Section: Discussionsupporting
confidence: 81%
“…Regarding the occurrence of left sided heart lesions and the potential progressive aspect in our patient of aortic dilatation, these features go along with previous reports that genes which belong to TGFβ cascade are potentially prone to this subcategory of cardiac involvement (Baban et al, 2018). It might be wise to establish a specific screening program through serial electrocardiography and echocardiography detect progressive aortic dilatation or arrhythmias.…”
Section: Discussionsupporting
confidence: 81%
“…Both our FMD2 patients showed phenotypes compatible with previously reported patients (Wade et al, 2017). Interestingly, our adult male FMD2 Regarding the occurrence of left-sided heart lesions and the potential progressive aspect in our patients of aortic dilatation, these features go along with previous reports that genes which belong to the TGF-β cascade are potentially prone to this subcategory of cardiac involvement (Baban et al, 2018;Caulfield et al, 2018;Cheng et al, 2017;Engwerda et al, 2021;Hanson et al, 2022;Yin et al, 2022). It might be wise to establish a specific screening program through serial electrocardiography and echocardiography detect progressive aortic dilatation or arrhythmias.…”
Section: Frontometaphyseal Dysplasia Typesupporting
confidence: 90%
“…4 Gonosomal mosaicism occurs in several heritable connective tissue disorders, for example Loeys-Dietz syndrome and Marfan syndrome. 5,6 In a study on 333 individuals with Marfan syndrome, around 5% of assumed de novo cases were caused by parental gonosomal mosaicism. 7 In the same study, a case with low-level parental mosaicism for a COL5A1 variant was reported for the first time.…”
Section: Discussionmentioning
confidence: 99%